Improving value in health care measuring quality. (OECD Health Policy Studies, 2010)
Are breast cancer survival rates higher in the United States than in the United Kingdom and France? Are a patient's chances of dying within 30 days after admission to a hospital with a heart attack lower in Canada than in Korea? Are surgeons in some countries more likely to leave "foreign bodies" behind after operations or make accidental punctures or lacerations rates when performing surgery? The need for answers to these kinds of question and the value of measuring the quality of health care are among the issues addressed in this publication.